2020
DOI: 10.4235/agmr.20.0012
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous Cryptococcosis in an Older Immunocompetent Patient: A Case Report

Abstract: Cryptococcus neoformans is an encapsulated yeast that can be found in decaying wood, hay, dust, and feces of birds, especially pigeons. 1) Cryptococcosis is considered an opportunistic infection in immunocompromised people, such as patients with malignancy, human immunodeficiency virus (HIV) infection, and those on long-term treatment with glucocorticoids and immunosuppressive agents after organ transplantation. 2) The infections mainly involve the lungs and central nervous system, with skin invasion considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In a local study, cryptococcosis was an HIV/AIDS-defining disease in 40% of cases, so it is important to rule out causes of immunosuppression associated with fungal infection [7]. On the other hand, systemic cryptococcosis in hosts without impairment of immune system is rare and PCC in these immunocompetent patients even more rarely described on the literature [2,[8][9][10][11][12][13][14][15][16]. Our case contributes to the scarce data; we show an immunocompetent patient, without any typical predisposition factor for cryptococcosis, that fulfilled all criteria for PCC diagnoses caused by C. neoformans [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a local study, cryptococcosis was an HIV/AIDS-defining disease in 40% of cases, so it is important to rule out causes of immunosuppression associated with fungal infection [7]. On the other hand, systemic cryptococcosis in hosts without impairment of immune system is rare and PCC in these immunocompetent patients even more rarely described on the literature [2,[8][9][10][11][12][13][14][15][16]. Our case contributes to the scarce data; we show an immunocompetent patient, without any typical predisposition factor for cryptococcosis, that fulfilled all criteria for PCC diagnoses caused by C. neoformans [1].…”
Section: Discussionmentioning
confidence: 99%
“…Kronstand, et al, reported that a high fungal load, to which the host is exposed, can explain the disease in immunocompetent persons, via the inhalation of a large number of infectious spores [17]. However, the route of exposure via traumatic inoculation seems more strongly related to PCC [4,16,[18][19][20]. Since the habitat of pigeons and other birds is a reservoir for Cryptococcus species in the environment, we believe this mycosis resulted from an occupational exposure in our case, as has already been described in the literature [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…12 While no definitive standard treatment protocol exists for PCC, fluconazole and itraconazole are commonly used to treat this condition, with their dose and treatment durations contingent on the patient's immune status and degree of involvement. 13,14 A treatment duration of 6-12 months is recommended by the Infectious Diseases Society of America (IDSA) for patients without dissemination and nervous system involvement. 3 There are reports of PCC in patients with lymphoma, leukaemia and rectal adenocarcinoma combined with multiple metastases who were treated with targeted drugs, immunosuppressive agents or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 12 While no definitive standard treatment protocol exists for PCC, fluconazole and itraconazole are commonly used to treat this condition, with their dose and treatment durations contingent on the patient’s immune status and degree of involvement. 13 , 14 A treatment duration of 6–12 months is recommended by the Infectious Diseases Society of America (IDSA) for patients without dissemination and nervous system involvement. 3 …”
Section: Discussionmentioning
confidence: 99%